2004
DOI: 10.1074/jbc.m401640200
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific Loading of an MCM Protein Complex in a DNA Replication Initiation Zone Upstream of the c-MYC Gene in the HeLa Cell Cycle

Abstract: The MCM proteins participate in an orderly association, beginning with the origin recognition complex, that culminates in the initiation of chromosomal DNA replication. Among these, MCM proteins 4, 6, and 7 constitute a subcomplex that reportedly possesses DNA helicase activity. Little is known about DNA sequences initially bound by these MCM proteins or about their cell cycle distribution in the chromatin. We have determined the locations of certain MCM and associated proteins by chromatin immunoprecipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 51 publications
4
45
0
Order By: Relevance
“…Similar effects were not observed on MCM6 or MCM7 (data not shown), suggesting that some MCM4 may move on or off chromatin independently of the core helicase complex. While MCM4, -6, and -7 are generally thought to function as a complex, at least two other studies in human cells have found that MCM4 can act independently from MCM6 and MCM7 (16,19). MCM4 has also been shown to assemble on chromatin independently from MCM2 and MCM3 in Xenopus egg extracts (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar effects were not observed on MCM6 or MCM7 (data not shown), suggesting that some MCM4 may move on or off chromatin independently of the core helicase complex. While MCM4, -6, and -7 are generally thought to function as a complex, at least two other studies in human cells have found that MCM4 can act independently from MCM6 and MCM7 (16,19). MCM4 has also been shown to assemble on chromatin independently from MCM2 and MCM3 in Xenopus egg extracts (4).…”
Section: Discussionmentioning
confidence: 99%
“…In human cells, the MCM subunits assemble on DNA beginning in late mitosis and remain associated with the chromatin until early G 2 , after DNA synthesis is completed (11,18,37). MCM proteins have also been shown to be preferentially loaded at human origins of replication and then distributed to more distal sequences during DNA synthesis (16,34). A similar pattern of cell cycle-dependent chromosome and origin association was observed for MCM-BP, consistent with the possibility that some MCM-BP is loaded onto DNA as part of an MCM complex.…”
Section: Discussionmentioning
confidence: 99%
“…The protein/DNA complexes from intact AD and AI cells or from minced frozen PC tissues were cross-linked and then lysed as previously described (30). Equal amounts of protein or tissue lysates (50-130 mg total weight) were incubated with the primary antibody, Pura 5B11 and 1A12 (31), followed by Protein G PLUS-Agarose beads (Santa Cruz), washed twice with high-salt buffer (0.5 mol/L NaCl), followed by LiCl/detergent solution and TE buffer.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP Assay and Re-precipitation (Re-ChIP)-Immunoprecipitation of formaldehyde cross-linked chromatin from the transfected SW13, C33a cells, and primary hepatocytes was performed using the ChIP assay kit (Upstate Biotechnology, Inc.) according to the manufacturer's instructions with some modifications (27,28). The immunoprecipitated DNAs and input DNA were analyzed by PCR using the following as primers: 5Ј-CATAACTTTAATGAATTGACAAAGC-3Ј and 5Ј-GAGAAACTCGCTCTAATATACTTCTC-3Ј for the rat albumin promoter; 5Ј-TTTTTGGCAAGGATGGTATG-3Ј and GLprimer2 (Promega) for the promoter region of the luciferase reporter plasmid (albumin promoter); 5Ј-GCACTGTG-CAGAAGAGCTGG-3Ј and 5Ј-CTGCAGCGGCGATCAGA-CCC-3Ј for the rat DHFR promoter; and 5Ј-AGGCTTCCGG-CGAGACATGGC-3Ј and 5Ј-ATGTTCTGGGACACAGCG-ACGATGC-3Ј for the human DHFR promoter.…”
Section: Methodsmentioning
confidence: 99%